Neuropati Optik Kompresif Bilateral yang Terinduksi oleh Schwannoma - Cinintha Nandini; Lukisiari Agustini (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2020)
The aim of this case report was to present further study about diagnosis and management of bilateral compressive optic neuropathy induced by schwannoma. This case report will discuss about the definition, classification, etiology, clinical diagnosis and treatment for compressive optic neuropathy. A case report. 43 years-old woman complained about blurred vision since 2 years ago. She also complained about pain on her right head while she was walking. There was no history of tinnitus or hearing loss. She had a history of contraception pill uses and progesterone injection every 3 months for 5 years alternately. She also suffered from schwannoma in cerebello pontine angle based on MRI and histopathology examination. From physical examination, best corrected visual acuity on right eye was 5/6 PHNI and on left eye was 5/8 PHNI. Ishihara test showed decreased colour vision. There was also ataxic gait. From anterior segment examination, there were decreased light reflex and RAPD. From posterior segment examination, there were papilloedema and elevation on both eyes proved by OCT and fundal imaging.  Neuroprotector therapy and surgery show a good result. Ishihara test are improving, light reflex are increasing and there are no RAPD anymore. From posterior segment, papilloedema are slowly diminished. The patient presents a case of bilateral compressive optic neuropathy induced by schwannoma. Neuroprotector and surgery show a good result.